Relationship Between Knowledge and Fasting Plasma Glucose Values of Patients with Type 2 Diabetes Mellitus at Sleman Public Health Center - Yunita Linawati; Damianus Andrian Putra Lere Kaka; Monica Vini Hildegadris Pandey; Angelica Chandra; Helen Angelique Julia Tukunang; Angel Pricillia Nathaly; Dhea Pricillia Fitriana; Imelda Maharani Eka Timur (Sanata Dharma University, 2025)
Diabetes Mellitus (DM) is a chronic disease caused by unstable blood sugar (glucose) levels, characterized by the body's inability to metabolize carbohydrates and fats. Unstable or uncontrolled blood sugar levels can be influenced by a lack of knowledge, which impacts the attitudes and behavior of people with DM. Controlling blood sugar levels in patients with DM is very important to avoid complications, both macrovascular and microvascular. The purpose of this study is to examine the connection between type 2 DM patients’ fasting plasma glucose (FPG) values and their degree of knowledge. This study was conducted at Mlati 2, Ngaglik 2, and Ngemplak 2 Health Centers of Sleman Regency Yogyakarta. This cross-sectional study used an analytical observational strategy. Purposive sampling was used to choose the 227 patients who participated in this study as respondents. The Diabetes Knowledge Questionnaire (DKQ-24) was the tool utilized in this study to gauge respondents’ knowledge levels and the outcomes of the FPG levels taken from medical records. The Spearman-rank test was used for data analysis with significance set as p0.05. The majority of patients, 99 (43.61%) had a moderate degree of knowledge and 207 (91.19%) had uncontrollable FPG levels. Based on bivariate analysis, there was no significant relationship between knowledge level and FPG values (p = 0.926), while the strength of the relationship was classified as a very low category (r = 0.006).